The impact of parameterising light penetration into snow on the photochemical production of NOx and OH radicals in snow - H. G. Chan; M. D. King; M. M. Frey (Atmospheric Chemistry and Physics, 2015)
Snow photochemical processes drive production of chemical trace gases in snowpacks, including nitrogen oxides (NOx = NO + NO2) and hydrogen oxide radical (HOx = OH + HO2), which are then released to the lower atmosphere. Coupled atmosphere–snow modelling of theses processes on global scales requires simple parameterisations of actinic flux in snow to reduce computational cost. The disagreement between a physical radiative-transfer (RT) method and a parameterisation based upon the e-folding depth of actinic flux in snow is evaluated. In particular, the photolysis of the nitrate anion (NO3-), the nitrite anion (NO2-) and hydrogen peroxide (H2O2) in snow and nitrogen dioxide (NO2) in the snowpack interstitial air are considered. The emission flux from the snowpack is estimated as the product of the depth-integrated photolysis rate coefficient, v, and the concentration of photolysis precursors in the snow. The depth-integrated photolysis rate coefficient is calculated (a) explicitly with an RT model (TUV), vTUV, and (b) with a simple parameterisation based on e-folding depth, vze. The metric for the evaluation is based upon the deviation of the ratio of the depth-integrated photolysis rate coefficient determined by the two methods, vTUV/vze, from unity. The ratio depends primarily on the position of the peak in the photolysis action spectrum of chemical species, solar zenith angle and physical properties of the snowpack, i.e. strong dependence on the light-scattering cross section and the mass ratio of light-absorbing impurity (i.e. black carbon and HULIS) with a weak dependence on density. For the photolysis of NO2, the NO2- anion, the NO3- anion and H2O2 the ratio vTUV/vze varies within the range of 0.82–1.35, 0.88–1.28, 0.93–1.27 and 0.91–1.28 respectively. The e-folding depth parameterisation underestimates for small solar zenith angles and overestimates at solar zenith angles around 60° compared to the RT method. A simple algorithm has been developed to improve the parameterisation which reduces the ratio vTUV/vze to 0.97–1.02, 0.99–1.02, 0.99–1.03 and 0.98–1.06 for photolysis of NO2, the NO2- anion, the NO3- anion and H2O2 respectively. The e-folding depth parameterisation may give acceptable results for the photolysis of the NO3- anion and H2O2 in cold polar snow with large solar zenith angles, but it can be improved by a correction based on solar zenith angle and for cloudy skies.